Analisys of The Effect of Fisherman, Fishing Boat, and Fishery Ports on Catching Fisheries Production in East Java Province - Aida, Gilang Rusrita; Illahi, Rhochmad Wahyu; Pramesthy, Tyas Dita (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
The importance of the fisheries sector for East Java Province can be seen from the high capture fisheries production compared to other provinces di Indonesia. In 2021, East Java Province is listed as the province with the highest capture fisheries production in Indonesia. This is suspected to be affected by several factors i.e the numberi of fishermen, fishing vessels, and fishing ports, so analysis is needed to determinei the effect of these factors on capture fisheries in East Java. The aim of this studyi was to determine the effect of the amount of fishermen, fishing boats, and fishing ports on capture fisheries production in East Java. The research methodi used in this research iis descriptive using secondary data. The data analysis used is multiplei linear regression, F-test, and T-test. Based on the results, the multiple linear regression analysis were obtained by the equation y = 292.543,118 + 0,381 X1-0,722 X2 + 2.838,450 X3 with an adjusted R2 value of 72,7 %. The F test shows a isignificance <0,05, which meansi that the total number of fishermen, fishing boats, and fishing ports have a significant effecti simultaneously on capture fisheries production in East Java. The T-test shows that the numberi of fishing ports has a partially significant effect on marine capture fisheries production in East Java Province (sig. <0,05). Meanwhile, the number ofi fishermen and fishingi boats showed no partially significant effect oni capture fisheriesi production in East Java Province (sig. > 0,05).